2009
DOI: 10.1038/nature08098
|View full text |Cite
|
Sign up to set email alerts
|

The pluripotency factor Oct4 interacts with Ctcf and also controls X-chromosome pairing and counting

Abstract: Pluripotency of embryonic stem (ES) cells is controlled by defined transcription factors1,2. During differentiation, mouse ES cells undergo global epigenetic reprogramming, as exemplified by X-chromosome inactivation (XCI) whereby one female X-chromosome is silenced to achieve gene dosage parity between the sexes3-5. Somatic XCI is regulated by homologous X-chromosome pairing6,7, counting8-10, and random choice of future active X (Xa) and inactive X’s. XCI and cell differentiation are tightly coupled11, as blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
268
1
7

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 264 publications
(290 citation statements)
references
References 30 publications
9
268
1
7
Order By: Relevance
“…Recombinational double-strand break repair and programmed homologous recombination during meiosis all involve complex series of biochemical reactions in which single-stranded DNA (ssDNA) plays a prominent role. There also exist homologous pairing reactions that seem to involve interactions between chromosomal regions whose DNAs are chemically intact double-stranded DNA (dsDNA) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). In some instances, whole chromosomes pair via multiple interactions all along their lengths (1)(2)(3)(4)(5)(6)(7)(8)(9) or via any region present in duplicate copies (10).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recombinational double-strand break repair and programmed homologous recombination during meiosis all involve complex series of biochemical reactions in which single-stranded DNA (ssDNA) plays a prominent role. There also exist homologous pairing reactions that seem to involve interactions between chromosomal regions whose DNAs are chemically intact double-stranded DNA (dsDNA) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). In some instances, whole chromosomes pair via multiple interactions all along their lengths (1)(2)(3)(4)(5)(6)(7)(8)(9) or via any region present in duplicate copies (10).…”
mentioning
confidence: 99%
“…In some instances, whole chromosomes pair via multiple interactions all along their lengths (1)(2)(3)(4)(5)(6)(7)(8)(9) or via any region present in duplicate copies (10). In other cases, pairing occurs preferentially or exclusively in particular localized regions (''pairing sites''), which tend to involve repeated sequences, specific proteins (for establishment and/or maintenance of pairing) and/or heterochromatic regions (characterized by a paucity of genes and a less ''open'' chromatin structure) (1,(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the stem cell transcription factor Oct4 has been implicated in the regulation of Xist expression in mice (Navarro et al, 2008;Donohoe et al, 2009). Oct4 has been shown to bind DNA sequences within Xist intron 1 and around the promoter and enhancer sequences of Tsix (Figure 2b).…”
Section: Inactivation In Mammals M Leeb and A Wutzmentioning
confidence: 99%
“…Recent studies further propose that the differential expression of Xist is spatio-temporally regulated between two X chromosomes prior to the onset of X-inactivation by a physical association of the Xic region referred to as 'pairing', suggesting a means by which two X chromosomes may communicate with one another prior to selecting a single X chromosome for silencing [19,20]. Other studies have suggested that pluripotency factors, which bind their recognition sequences present in potential regulatory regions of Xist and Tsix, balance their expression to suppress or induce X-inactivation in a developmentally regulated manner [21][22][23]. More recently, an X-linked factor, Rnf12, has been shown to have a role in ensuring that Xist is activated only on a single X chromosome in female cells [24].…”
Section: Introductionmentioning
confidence: 99%